Pulse oximetry as a screening tool for congenital heart disease in neonates: A diagnostic study - Panda, Prakash Chandra; Mishra, Nihar Ranjan; Dash, Shovendra Kumar; Nayak, Bijan Kumar; Panda, Kanhu (Indian Journal of Child Health, 2019)
Introduction: Many studies have been done for screening of congenital heart disease (CHD) in the neonatal period utilizing pulse oximetry as a screening tool along with routine clinical assessment, but none of them from our province. Objective: The objective of the study was to find out the diagnostic accuracy of pulse oximeter at three different sites as a screening tool to diagnose CHD among neonates. Methods: A diagnostic study was conducted in neonatal intensive care unit of a tertiary care hospital of Odisha from October 2016 to September 2018 after approval from the Institutional Ethics Committee. Three hundred and seventy-four neonates (both inborn and outborn) with gestational age >34 weeks were included in the study. Oxygen saturation (SpO2) in the right hand (RH), right foot (RF), and left foot (LF) was estimated by pulse oximeter among all participants after 10 min of postnatal life. All the study subjects were evaluated by two-dimensional (2D) echocardiography for the detection of CHDs. All the diagnostic accuracy tests (sensitivity [Sn], specificity [Sp], positive predictive value, negative predictive value, and diagnostic odds ratio) were calculated taking 2D echocardiography as the gold standard with software, and for all statistical purpose, p<0.05 was considered statistically significant. Results: Cutoff value of the RH SpO2 was 90.0% with Sn of 68.80% and Sp of 98.20%; area under curve (AUC) 0.851 (0.766 and 0.914), p<0.001, for the RF, SpO2 was 90.0% with Sn 78.0% and Sp 92.1%; AUC 0.865 (0.782 and 0.925), p<0.001, and for LF, it was 87% with Sn 77.1% and Sp 94.0%; AUC 0.864 (0.781 and 0.924), p<0.001. Conclusion: Along with the clinical skills, pulse oximetry can be used as an early screening tool for the detection of CHD in the neonatal period and of three different sites, RF found to be better.